2016
DOI: 10.1111/coa.12506
|View full text |Cite
|
Sign up to set email alerts
|

Participation in sport and physical activity in head and neck cancer survivors: associations with quality of life

Abstract: These data suggest that PA may improve QOL following treatment for HNC. We believe that further studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 40 publications
7
23
0
Order By: Relevance
“…Smoking, alcohol consumption and infection with the human papillomavirus (HPV) are the most common risk factors for developing HNC [2]. Observational studies showed that higher levels of physical activity following the diagnosis and treatment of cancer and higher levels of physical fitness before the diagnosis of cancer are associated with reduced mortality [2][3][4] and better quality of life [5], but the relationship is not uniform, may differ by the type of cancer. Based on these studies, it seems clear that levels of physical activity and fitness play an important role in the risk of cancer, the quality of life of patients with cancer and mortality in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking, alcohol consumption and infection with the human papillomavirus (HPV) are the most common risk factors for developing HNC [2]. Observational studies showed that higher levels of physical activity following the diagnosis and treatment of cancer and higher levels of physical fitness before the diagnosis of cancer are associated with reduced mortality [2][3][4] and better quality of life [5], but the relationship is not uniform, may differ by the type of cancer. Based on these studies, it seems clear that levels of physical activity and fitness play an important role in the risk of cancer, the quality of life of patients with cancer and mortality in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is a behavior that includes occupational, leisure, household or other activities, whereas health-related physical fitness is a set of attributes that people have or achieve and which includes cardiorespiratory fitness and muscle strength [6]. Previous retrospective studies showed that 31% of patients with HNC met the current physical activity guideline pre-diagnosis, which decreased to 8.5% after diagnosis [7] and declines further during treatment [5,8,9]. However, all these studies measured physical activity through self-report, which is prone to bias [10] and likely to over-or underreport physical activity levels [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also reported decreases in physical function and QOL after HSCT, compared to pre‐transplantation levels, in patients having undergone allo‐HSCT (Takekiyo et al., ; Wiskemann et al., ). Although the relationship between physical activity and QOL has been evaluated in patients with breast cancer (Pakiz et al., ), gastrointestinal cancer (Jensen et al., ), ovarian cancer (von Gruenigen et al., ), prostate cancer with radical prostatectomy (Santa Mina et al., ), lung cancer (Wang et al., ), head and neck cancer (Sammut, Fraser, Ward, Singh, & Patel, ), colorectal cancer (Grimmett, Bridgewater, Steptoe, & Wardle, ), and kidney cancer (Trinh, Plotnikoff, Rhodes, North, & Courneya, ), the relationship of physical activity with physical function and health‐related QOL in patients having undergone allo‐HSCT remains to be evaluated. Therefore, we investigated the differences in the intensity levels of physical activity, physical function, and health‐related QOL before and after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies showed that higher levels of moderate-to-vigorous PA are associated with lower mortality risk in survivors of breast, colon, and prostate cancer [ 19 , 21 , 25 , 30 , 38 ]. Also in HNC survivors, higher pre-treatment levels of PA and physical function were found to be associated with higher HRQoL [ 6 , 36 ] and survival [ 10 , 43 ].…”
Section: Introductionmentioning
confidence: 99%